Prediction of Fatigue Life of Coil Springs and Lower Suspension Arms Based on Strain-Life Approach - Lim, Sokha (Journal of Engineering and Science, 2025)
This study predicts the fatigue life of helical coil springs and lower suspension arms in automotive suspension systems using the strain-life approach. The strain-life method, which incorporates local plastic strain effects, is particularly suitable for components experiencing variable amplitude loading under road-induced vibrations. Finite element analysis (FEA) was employed to determine critical strain locations and magnitudes under typical loading conditions. Fatigue life was estimated using the Coffin-Manson relation, with mean stress corrections via the Morrow and Smith-Watson-Topper (SWT) models. Results indicate that coil springs exhibit fatigue lives ranging from 10⁵ to 10⁶ cycles under rural road excitations, while lower suspension arms show shorter lives at high-stress regions due to multiaxial loading. The findings highlight the importance of material selection and geometry optimization for improved durability in automotive applications